ENSO's Changing Influence on Temperature, Precipitation, and Wildfire in a Warming Climate - Fasullo, J. T.; Otto‐Bliesner, B. L.; Stevenson, S. (Geophysical research letters, 2018)
On interannual to decadal time scales, the climate mode with many of the strongest societal impacts is the El Niño–Southern Oscillation (ENSO). However, quantifying ENSO's changes in a warming climate remains a formidable challenge, due to both the noise arising from internal variability and the complexity of air‐sea feedbacks in the tropical Pacific Ocean. In this work, we use large (≥30‐member) ensembles of climate simulations to show that anthropogenic climate change can produce systematic increases in ENSO teleconnection strength over many land regions, driving increased interannual variability in regional temperature extremes and wildfire frequency. As the spatial character of this intensification exhibits strong land‐ocean contrasts, a causal role for land‐atmosphere feedbacks is suggested. The identified increase in variance occurs in multiple model ensembles, independent of changes in sea surface temperature variance. This suggests that in addition to changes in the overall likelihoods of heat and wildfire extremes, the variability in these events may also be a robust feature of future climate. Plain Language Summary Changes in climate variability strongly affect the overall impacts of climate change. In this work, increases in the intensity of heat waves and wildfire driven by El Niño/La Niña in a business‐as‐usual climate scenario are identified in recently produced climate simulations spanning the 20th and 21st centuries. The intensification in temperature extremes occurs mainly over land regions and independently of changes in eastern Pacific sea surface temperature variability. It is argued that land atmosphere feedbacks are likely to play a key role in the simulated amplification, with relevance to impacts such as heat waves and wildfire frequency. Key Points Intensity increases in temperature and wildfire extremes driven by ENSO in a warming climate are identified in climate model large ensembles The intensification occurs mainly over land regions and is influenced by precipitation Land‐atmosphere feedbacks are likely to play a key role in the projected amplification